Some physical properties of mature green Nipah and Nangka banana fruit - Zainal A'bidin, Farahana Nabilah; Shamsudin, Rosnah; Mohd Basri, Mohd Salahuddin; Mohd Dom, Zanariah (Malaysian Society of Agricultural Engineers, 2019)
Physical properties of fruits and vegetables are important as it is used as a grading measurement for packaging and safe transportation. The postharvest losses of fruits are mainly due to its mechanical damage during transport and handling. Banana for example, has various varieties with different shapes and sizes. Therefore this study was conducted to assess some physical properties of mature green Nipah and Nangka banana fruit. Properties obtained were weight of whole fruit, peel and pulp, dimensions, surface area and projected area. The average weight, length and diameter of Nangka is higher than that of Nipah (p<0.05). Peel thickness of Nipah is higher than Nangka. The volume (Vellip), projected area (Pellip) and surface area (Sellip), Nangka possess higher value than Nipah.